Knowledge mapping of exosomes in metabolic diseases: a bibliometric analysis (2007-2022) - Xu, Fangzhi; Xia, Chenxi; Dou, Lin; Huang, Xiuqing (Frontiers in Endocrinology, 2023)
Background: Research on exosomes in metabolic diseases is receiving increasing attention and has significant value and potential. However, there is a lack of comprehensive and objective reports on the current state of research in this area. Therefore, the aim of this study was to conduct a bibliometric analysis on the topic of "exosomes in metabolic diseases" and to analyze the current status and trends of research through visualization. Methods: The web of science core collection was searched for publications on exosomes in metabolic diseases from 2007 to 2022. Three software packages, VOSviewer, CiteSpace, and R package "bibliometrix" were used for the bibliometric analysis. Results: 532 papers were completed by 29705 authors from 46 countries/regions and 923 institutions, published in 310 academic journals. The number of publications related to exosomes in metabolic diseases is gradually increasing. China and the United States are the most productive countries, while Ciber Centro de Investigacion Biomedica en Red is the most active institution. the International Journal of Molecular Sciences published the most relevant studies, and Plos One received the most citations. Khalyfa, Abdelnaby published the most papers and Thery, C was the most cited. The ten most co-cited references were considered as the knowledge base. After analysis, the most common keywords were microRNAs, biomarkers, insulin-resistance, expression, and obesity. Applying basic research related on exosomes in metabolic diseases to clinical diagnosis and treatment is a research hotspot and trend. Conclusion: This study is the first comprehensive summary of research trends and developments in exosomes in metabolic diseases through bibliometrics. The information points out the research frontiers and hot directions in recent years and will provide a reference for researchers in this field.